The Role of History Teachers in Improving the Nationalism Attitude of Students of Class XI IPS SMA Negeri 1 Juwana Pati - Sari, Ria Erlita; Muntholib, Abdul (Universitas Negeri Semarang, 2016)
This study aims to (1) find out the manifestation of students' nationalism attitudes in daily life, (2) describe the role of history teachers in improving students' nationalism attitudes, and (3) find out the obstacles faced by history teachers in improving students' nationalism attitudes. The method used in this research is qualitative, taking the research setting at SMA Negeri 1 Juwana, Pati Regency. Data collection techniques used interviews, observation, and documentation. The data analysis used was interactive data analysis. Data validity was checked by triangulation technique. The study results are as follows: (1) the embodiment of students' nationalism attitude in daily life students study diligently, love the environment, are disciplined to follow school activities, use domestic products, and respect the opinions of others. (2) The role of history teachers in trying to improve students' nationalism is that teachers have a role as role models, mentors, teachers, inspirers, authorities, and evaluators. (3) The obstacles teachers face are the development of globalization, different family background factors, and the wide association of students.